1998
DOI: 10.1038/bjc.1998.264
|View full text |Cite
|
Sign up to set email alerts
|

γ-Linolenic acid (GLA) is cytotoxic to 36B10 malignant rat astrocytoma cells but not to 'normal' rat astrocytes

Abstract: Summary This study compares the effect of y-linolenic acid (GLA) and its precursor linoleic acid (LA) on survival of 36B10 malignant rat astrocytoma cells and 'normal' rat astrocytes. GLA was cytotoxic to 36B10 cells but not to astrocytes. By contrast, LA supplementation did not affect the survival of either cell types. There were minor differences in the uptake, distribution and use of radiolabelled GLA and LA by the 36B1 0 cells and astrocytes. GLA and LA supplementation increased the total polyunsaturated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
4

Year Published

2003
2003
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 39 publications
1
39
0
4
Order By: Relevance
“…39 Several investigations have shown that micromolar concentrations of PUFAs such as DHA or eicosapentaenoic acid may exert selective cytotoxicity on malignant tumor cells in vitro. [40][41][42][43][44][45][46][47][48] In addition, it has been shown that exogenously added PUFAs may sensitize tumor cells to ROSinducing anticancer agents both in vitro and in vivo. 31,32 For instance, it could be demonstrated that DHA significantly enhances the cytotoxicity of doxorubicin in the human breast tumor cell line MDA-MB-231 whereas no enhancing effect is observed for mitoxantrone, a drug with low ROS-generating potential.…”
Section: Discussionmentioning
confidence: 99%
“…39 Several investigations have shown that micromolar concentrations of PUFAs such as DHA or eicosapentaenoic acid may exert selective cytotoxicity on malignant tumor cells in vitro. [40][41][42][43][44][45][46][47][48] In addition, it has been shown that exogenously added PUFAs may sensitize tumor cells to ROSinducing anticancer agents both in vitro and in vivo. 31,32 For instance, it could be demonstrated that DHA significantly enhances the cytotoxicity of doxorubicin in the human breast tumor cell line MDA-MB-231 whereas no enhancing effect is observed for mitoxantrone, a drug with low ROS-generating potential.…”
Section: Discussionmentioning
confidence: 99%
“…Clonogenic survival assays were performed as described previously (Vartak et al, 1998). Two hundred and fifty to 2000 cells were plated in 60 mm dishes and incubated overnight.…”
Section: Clonogenic Survival Assaymentioning
confidence: 99%
“…The mouse embryo fibroblasts were maintained in DMEM containing 10% FBS, 4 mM l -glutamine, 50 g/ml gentamycin, and 4.5 g/l glucose. Cell viability was determined using the commercially available calcein AM reagent obtained from Molecular Probes (Eugene, OR) according to the specifications of the supplier (13,14).…”
Section: Cell Culturementioning
confidence: 99%
“…This patient developed clinical symptoms characteristic of essential fatty acid deficiency shortly after birth, and GLC analysis of her plasma fatty acid composition indicated low levels of both arachidonic acid and DHA. We demonstrated that cultured skin fibroblasts obtained from this patient converted 85% to 95% less [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]linoleic acid to arachidonic acid than corresponding normal fibroblast cultures (5). Our results also indicated that the conversion of radiolabeled PUFA precursors to DHA was markedly reduced in the patient's fibroblasts.…”
mentioning
confidence: 99%